INFECTIONS OF THE NEWBORNS: ETIOLOGY AND EPIDEMIOLOGY - Valeriu Popescu (Amaltea Medical Publishing House, 2008)
Infections are a frecvent and important cause of morbidity and mortality in the newborn period. Infections in the newborn infant may be required in utero (congenital), at the terme/or birth (perinatal), or after birth and during the neonatal period (postnatal). The transplacental route is the most common means by which microorganisms reaches the fetus in utero. Some viruses, Toxoplasma gondii, Treponema pallidum, and occasionally other bacteria are transmitted by this route. Infection acquired in utero may result in resorption of the embryo, absorbtion, stillbirth, congenital malformations, intrauterine growth retardation, premature birth, acute diseases in the immediate neonatal, prenatal, or on asymptomatic, but persistent infection that cause neurologic sequelae later in life. Further on the author presents: - viral infections: rubella virus, cytomegalovirus, herpes virus hominis, hepatitis B, Coksackie, HIV, measles virus, mumps virus, varicella-zoster virus; - bacterial infections; - rickettiene infections; - infections with mycoplasme and chlamydia; - mycotic infections; - protozoar infections (toxoplasma, malaria, leishmaniasis - Kala - Azar, trypanosomiasis); - parasitic infections (echinococosis, schistosomiasis, ankilostomiasis).